Modeling of iron losses of permanent-magnet synchronous motors - Chunting Mi; Slemon, G.R.; Bonert, R. (IEEE transactions on industry applications, 2003)
Permanent-magnet (PM) motors offer potential energy savings as compared with induction motors because of the virtual elimination of rotor loss and the reduction of stator loss from operation near unity power factor. In PM machines, iron losses form a significant fraction of the total loss partly due to the nonsinusoidal flux density distribution. Design optimization therefore requires good means of predicting these iron losses. Finite-element analysis can be employed but this approach is cumbersome and costly when used in the many iterations needed in optimizing the design. This paper presents a set of improved approximate models for the prediction of iron loss. They can be used in design optimization programs and, since they are directly related to machine dimensions and material properties, they also provide quick insight into the effects of design changes. A time-stepped finite-element method is employed to evaluate the iron losses in a range of typical PM machines and the results are used to evaluate the adequacy of the models. The predictions of overall iron losses are then compared with measurements made on two PM motors.